Economic Analysis of Carrot (Daucus carota L.) Under Seed Priming and Pelleting in Combination with Different Crop Geometry - Sharma, Pramod; Thakur, Ashok Kumar; Kumar, Sanjeev (International Journal of Economic Plants, 2020)
The present study was conducted at experimental farm of Department of Seed Science and Technology, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.) during the years 2017-18 and 2018-19 under priming and pelleting in combination with different crop geometry to improve carrot production for maximizing economic returns. The economics of carrot under different treatment combinations was worked out to find theaving osmotic potential of -1.2 MPa and pelleted with Melia azedarach leaf powder sown at paired row 30 +15 x 10 cm (T1G2) was more profitable as compare to other treatment combinations as net returns as well as BC ratio (2.31) was higher under this combination as compare t most economical treatment combination. It was concluded that the treatment combination seed primed for 4 days in PEG 6000 solution ho other treatment combinations.